2005
DOI: 10.1364/ol.30.002596
|View full text |Cite
|
Sign up to set email alerts
|

Controlled induction, enhancement, and guidance of neuronal growth cones by use of line optical tweezers

Abstract: We report an optical tweezers based approach for efficient and controlled manipulation of neuronal growth cones. The approach exploits asymmetric transverse gradient force created in a line optical tweezers to transport actin monomers in the desired growth direction. With this approach induction of artificial growth cones from the neuronal cell body and enhancement of the growth rate of the natural growth cones have been achieved. The use of this approach to bring two growth cones into close proximity for esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 10 publications
3
38
1
Order By: Relevance
“…Previous estimates of this effect in the optical neuronal guidance experiments suggested a negligible temperature increase (Albrecht-Buehler, 1991;Carnegie et al, 2008Carnegie et al, , 2009Ehrlicher et al, 2002;Graves et al, 2009;Higuchi et al, 2005Higuchi et al, , 2007Mohanty et al, 2005;Stevenson et al, 2006;Mathew et al, 2010;Koch et al, 2004), but our more detailed simulations show a temperature increase of the order 1 • C/100 mW of laser power, which is in agreement with experimental results and modelling from the field of optical trapping (Schönle and Hell, 1998;Braun and Libchaber, 2002;Peterman et al, 2003;Ebert et al, 2007). Furthermore, we find a temperature gradient of the order 1 • C/typical neuronal growth cone-radius.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous estimates of this effect in the optical neuronal guidance experiments suggested a negligible temperature increase (Albrecht-Buehler, 1991;Carnegie et al, 2008Carnegie et al, , 2009Ehrlicher et al, 2002;Graves et al, 2009;Higuchi et al, 2005Higuchi et al, , 2007Mohanty et al, 2005;Stevenson et al, 2006;Mathew et al, 2010;Koch et al, 2004), but our more detailed simulations show a temperature increase of the order 1 • C/100 mW of laser power, which is in agreement with experimental results and modelling from the field of optical trapping (Schönle and Hell, 1998;Braun and Libchaber, 2002;Peterman et al, 2003;Ebert et al, 2007). Furthermore, we find a temperature gradient of the order 1 • C/typical neuronal growth cone-radius.…”
Section: Introductionsupporting
confidence: 91%
“…A curious new addition to the field of neuronal guidance is optical neuronal guidance (Carnegie et al, 2008(Carnegie et al, , 2009Ehrlicher et al, 2002;Graves et al, 2009;Higuchi et al, 2005Higuchi et al, , 2007Mohanty et al, 2005;Stevenson et al, 2006;Mathew et al, 2010;Koch et al, 2004) reviewed in Franze and Guck (2010) and Stevenson et al (2010). In 1991 it was first observed that Swiss 3T3 cells (mammalian fibroblast-like cells) would extend pseudopodia towards near-infrared light sources (Albrecht-Buehler, 1991), and in 2002 it was shown that a near-infrared laser spot placed on and in front of the leading edge of growing PC12 and NG108 neurons enhanced the neuronal growth into the laser spot and resulted in laser-guided turns of the growth cone and increased growth speed (Ehrlicher et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This optical-guiding process occurs as the light pools actin monomers and provides nucleation sites for actin polymerization, which is the driving force for neuronal growth (Ehrlicher et al 2002;Dent & Gertler 2003). Other cell types reported for this optical-guiding process include N1E-115 cells from a neuroblastoma tumour (Mohanty et al 2005b), NG108, a rat/mouse hybrid neuroblastoma cell line that produces active growth cones (Stevenson et al 2006), as well as primary embryonic chicken retina cells (Stuhrmann et al 2006).…”
Section: Laser Scissors/scalpels and Opto-injectionmentioning
confidence: 99%
“…The main hypothesis in this work is that a tweezing-light like effect seems to gather chemical components at a certain location, enhancing local growth. With this idea in mind, axonal guidance was also achieved using an elliptical beam profile to better direct the optical forces in a chosen direction (Mohanty et al 2005). In addition, the attraction efficiency while guiding axons with laser light has been tested for different wavelengths (Stevenson et al 2006).…”
Section: Introductionmentioning
confidence: 99%